Rate of Retinal Re-Detachment Following Phacoemulsification and Silicone Oil Removal (Journal of Fatima Jinnah Medical University, 2018)
Background: Silicone oil injection is a common internal tamponading agent used in retinal attachment surgeries. However it can result in ocular complications like cataract, glaucoma and keratopathy. As soon as retina gains stability it is advisable to remove oil form vitreous cavity. The objective of the study is to evaluate the rate of retinal re-detachment following combined phacoemulsification, intraocular lens implantation and silicone oil removal.Study Design: prospective, interventionalMethods: 20 eyes of 20 patients with previous history of retinal detachment surgery (pars plana vitrectomy and silicone oil 1000 cst) were operated again once the retina was anatomically stable mean 9±2 SD months after previous retinal surgery. Phacoemulsification with foldable hydrophobic intraocular lens with silicone oil removal using Alcon Accurus Vitrectomy oil ejection system via 23 or 25 gauge pars plan approach was used. Patients were followed up on day 1, 1 month and 6 months postoperative and assessed for visual improvement plus retinal re detachment. Visual acuity, intraocular pressure, anterior and posterior examination using slit lamp and indirect ophthalmoscope was done on each visit. All surgeries (1st and 2nd) were done at single tertiary hospital of Lahore by one surgeon.Results: 60% males and 40% females in the study group with mean age of 41±15 years. The interval between the two surgeries was 8 to 12 months with mean of 9±2 SD. Visual acuity improvement of at least 2 lines was recorded in majority of patients at the end of last (6 month) follow-up. Temporary hypotony was recorded in first post op day with mean of 11.8±4.5 from pre-op pressure of 17.2±2.4 mmHg which was significant reduction with p-value
Keywords: Phacoemulsification, silicone oil, rhematogenous retinal detachment, traction retinal detachment, proliferative vitreoretinopathy PVR